If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+16=0x-12
We move all terms to the left:
6x+16-(0x-12)=0
We add all the numbers together, and all the variables
6x-(x-12)+16=0
We get rid of parentheses
6x-x+12+16=0
We add all the numbers together, and all the variables
5x+28=0
We move all terms containing x to the left, all other terms to the right
5x=-28
x=-28/5
x=-5+3/5
| 7|4n+8|-6=106 | | 63+9x=90 | | 2(x+2)+3=3(x-3)+12 | | 0=5/3x | | Mx2=1 | | e+7=12 | | x+2x+27+1/2(2x+27)+15+x-20+2(X-20)=2393 | | x4-24x2-25=0 | | 19=10-5w | | 11x+1=27+7x-2 | | 11x+1=27+7x-2= | | /5+x2=2x2+13 | | 187+x=374 | | (x-1)/3x=(x-2)/(3x-2) | | 4x=3=17 | | 12x=112 | | -4w(3w-1)=461 | | (x-1)/(3x)=(x-2)/(3x-2) | | -4w(3w-1)=0 | | 2x+2x+10=50 | | 19=x+23 | | 7x+6+22=9x+12 | | 7x+6+22=9x+12=180 | | 2x-18=3x-x-45 | | 7x+6+22+9x+12=180 | | +(x-4)=2x+6 | | 2(3y-7)=-20 | | 2x-13+2x+18+x=180 | | 2x-183x-45=0 | | 6(3p)²=p | | 2g+10=10 | | p=6(3p)² |